P111: Introduction of an ECPR protocol to paramedics in Atlantic Canada; a pilot knowledge translation project. (May 2019) - Rouse, C.; Mekwan, J.; Atkinson, P.; Fraser, J.; Gould, J.; Rollo, D.; Middleton, J.; Pishe, T.; Howlett, M.; Legare, J.; Chanyi, S.; Tutschka, M.; et al.
Abstract : Introduction : There is currently no protocol for the initiation of extra corporeal cardiopulmonary resuscitation (ECPR) in out of hospital cardiac arrest (OHCA) in Atlantic Canada. Advanced care paramedics (ACPs) perform advanced cardiac life support in the prehospital setting often completing the entire resuscitation on-scene. Implementation of ECPR will present a novel intervention that is only available at the receiving hospital, altering how ACPs manage selected patients. Our objective is to determine if an educational program can improve paramedic identification of ECPR candidates.Methods : An educational program was delivered to paramedics including a short seminar and pocket card coupled with simulations of OHCA cases. A before and after study design using a case-based survey was employed. Paramedics were scored on their ability to correctly identify OHCA patients who met the inclusion criteria for our ECPR protocol. Scores before and after the education delivery were compared using a two tailed t-test. A 6-month follow-up is planned to assess knowledge retention. Qualitative data was also collected from paramedics during simulation to help identify potential barriers to implementation of our protocol in the prehospital setting.Results : Nine advanced care paramedics participated in our educational program. Mean score pre-education was 9.7/16 (61.1%) compared to 14/16 (87.5%) after education delivery. The mean difference between groups was 4.22 (CI = 2.65-5.80, p = 0.0003). There was a significant improvement in the paramedics' ability to correctly identify ECPR candidates after completing our educational program.Conclusion : Paramedic training through a didactic session coupled with a pocket card and simulation appears to be a feasible method of knowledge translation. 6-month retention data will help ensure knowledge retention is achieved. If successful, this pilot will be expanded to train all paramedics in our prehospital system as we seek to implement an ECPR protocol at our centre.